KONSEKUENSI YURIDIS PENGGARAP LIAR PADA TANAH HGU PTPN II (STUDI DI PASAR XII DESA BANDAR KLIPPA KECAMATAN PERCUT SEI TUAN, KABUPATEN DELI SERDANG) - DAVID YAMIN DHARMA PUTRA (PREMISE LAW JURNAL, 2015)
Basically, UUPA (Agrarian Law) No. 5/1960 about Regulation Of The Basic Principles Agrarian does not regulate arable land becausse it does not have any land rights status. The legal sources which regulate thetillers’ rights are Law No. 2/1960 on Production Sharing Agreement between the Owner and Tillers. Law No. 51/1960 on Prohibition Of Land Use Without Permission Is Entitled or their proxies, Government Regulation No. 224/1961 on Division Of Land And Grant Of Compensation and Keppres No. 34/2003 on National Policy In The Field Of Land. Since outlawed tillers and their arable are basically illegal, the problem of the tilling right can be settled according to the notification of the history of the land in the land in the village Office. Witnesses on the land boundaries are asked to trace the history of the land, along with any land certificates. In general, all types of transfer of the tilling right on arable land will be registered in the village land book so that it can be seen in it the valid SKT (Letter of Notification on Land) issued by the village Administration. The Land history of Pasar XII of Bandar Klippa , Percut Sei Tuan Subdistrict, is the area of the residential land of more than 176,252 (one hundred seventy six thousand two hundred and fifty two) hectares, adjacent to PTPN II plantation which has its HGU (Leasedhold). This residential land is given to the people at Pasar XII of Bandar Klippa Village by PTPN II, for they are ex-workers of PTPN II which use to be PTP IX. They hold the land rights according to the Letter of PTPN II is under Article 385 of the Penal Code. Besides that, BPN (National Land Board) can also play its role in handling and settling the dispute in the HGU arable land of PTPN II through mediation, based on the mechanism of the Regulation of the Head of BPN RI No. 3/2011 on Assessment and Case Management of Land Management.